2011
DOI: 10.1021/jp108771h
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Quartz Crystal Microbalance Study of Borohydride Electro-Oxidation on Pt: The Effect of Borohydride Concentration and Thiourea Adsorption

Abstract: A systematic investigation of BH 4 electrooxidation in 2 M NaOH on Pt was carried out using the electrochemical quartz crystal microbalance technique (EQCM). Four sets of experiments were conducted: (i) Pt in NaOH, (ii) BH 4-(between 10 and 60 mM) on Pt, (iii) thiourea (TU) on Pt, and (iv) BH 4in the presence of TU (between 0.01 and 2.1 mM) on Pt. The BH 4 electro-oxidation mechanism was developed by correlating the EQCM results with density functional theory (DFT) calculations from the literature revealing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 51 publications
6
45
1
Order By: Relevance
“…The magnitude of the relative m decrease is equal to approximately −4.5 × 10 6 ng m −2 for either 20 mM or 60 mM BH 4 − concentrations and is comparable to the response observed on Pt in 60 mM BH 4 − . 6 In the latter case, due to the incomplete oxidation of BH 4 − on Pt there was evidence to suggest that peak C 3 is generated by the oxidation of adsorbed intermediates. 6 In case of Au, the existence of partial oxidation products at the outset of the return scan is less likely because on the anodic scan at high potentials complete oxidation is achieved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitude of the relative m decrease is equal to approximately −4.5 × 10 6 ng m −2 for either 20 mM or 60 mM BH 4 − concentrations and is comparable to the response observed on Pt in 60 mM BH 4 − . 6 In the latter case, due to the incomplete oxidation of BH 4 − on Pt there was evidence to suggest that peak C 3 is generated by the oxidation of adsorbed intermediates. 6 In case of Au, the existence of partial oxidation products at the outset of the return scan is less likely because on the anodic scan at high potentials complete oxidation is achieved.…”
Section: Resultsmentioning
confidence: 99%
“…In case of BH 4 − oxidation, EQCM was first employed by the present group using Pt electrode. 6 The goal here was to validate the EQCM technique for the electrooxidation of BH 4 − on the Au.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic voltammograms performed with the Pt electrode ( Fig. 2a) showed two oxidation waves in the anodic direction, similar to an analogous aqueous system [7]; however the oxidation waves are much broader. The highest BH 4 À oxidation currents and the most negative oxidation onset potential are observed on the oxidized Ni electrode (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Experimental and theoretical studies have shown that the electrooxidation of borohydride involves a number of competitive electrocatalytic and thermocatalytic pathways, which can diminish the Faradaic equivalence from eight to four electrons per mol of borohydride converted, depending on the electrocatalyst, electrode potential, temperature, and OH À /BH 4 À ratio. [5][6][7][8][9][10] Gyenge and co-workers demonstrated that osmium nanoparticles are promising candidates as alternatives for platinum electrocatalysts in DBFCs because they cost significantly less and exhibit high catalytic activity for the electrooxidation of borohydride. [9,[11][12][13] DBFC experiments that use an Os/C catalyst-coated Nafion 117 membrane revealed that at 298 K, in both the kinetic and mass-transport regions of the polarization curves, the borohydride electrooxidation on 20 wt % Os/C was superior to commercial 20 wt % Pt/C and Pt-Ru/C.…”
Section: Introductionmentioning
confidence: 99%